Social media and cadaveric dissection: A survey study. Issue 8 (25th June 2019) - Rai, Rabjot; Shereen, Rafik; Protas, Matthew; Greaney, Clara; Brooks, Katherine N.; Iwanaga, Joe; Loukas, Marios; Tubbs, R. Shane
Abstract : The use of social media opens content to the general public and, as a result, places images of cadaveric dissection in an open forum. This raises the question: should the general public have access to such material? A survey was conducted examining whether the general public should have access to gross cadaveric dissection images and videos for educational purposes via social media. Both medical and laypersons were queried. Questions included in the survey considered whether images were too graphic, whether online cadaveric content should be age‐restricted, and whether consent by the deceased was necessary. A link to the survey was accessible to 63, 562 followers through the Seattle Science Foundation's Facebookpage for 3 weeks. Among 300 responders, 89% (267/300) agreed that portrayals of cadaveric specimens/dissection on social media should be accessible by the general public for anatomical education, and 84.67% (254/300) stated that cadaveric dissection is not too graphic for untrained eyes. There was agreement by 60.33% (181/300) that an age restriction should be in place for the viewing of cadaveric dissection on social media, and 39.33% (253/300) of responders suggested restriction to 18 years and older. No statistically significant association was noted between a prior or current history of anatomy education and the frequency of positive responses to the survey questions. Social media is an innovative tool for dispensing anatomical education. The use of cadaveric images and videos provides accessibility to the general public who wish to learn more about human anatomy and their own body. Clin. Anat. 32:1033–1041, 2019. © 2019 Wiley Periodicals, Inc.